(untitled) - Steenburgen, Mary; 1946-; Bergen, Candice; 1937-; Fonda, Jane; Holderman, Bill; Keaton, Diane; Paramount Pictures Corporation (Hollywood, CA, 2018)
Four lifelong friends lives are turned upside down when their book club attempts to shake things up by tackling the infamous "Fifty Shades of Grey". From discovering new romance to rekindling old flames, they inspire each other to make their next chapter the best chapter.
Keywords: Female friendship; Drama; Book clubs (Discussion groups); Drama; Feature films; Comedy films